Taksa sądu ziemskiego w Oleśnicy z ostatniej dekady XVI wiek - Ptak, Marian J. (Studia Iuridica Toruniensia, 2012)
<!–[if gte mso 9]> <![endif]–> The author presents the oldest text of court fi xed pries the Duchy of Oels and attempts to interpretation it based on existing research results over regime of the courts this duchy. Proves that it is a fi xed pries terrestrial court of polish law in capital Olesnica written after 1591 and before 1593 year, after taken the off ice of judge by Caspar von Falkenberg auf Nietsche (Nieciszów). It follows that in the frame of this court – except courtly judge called still in that time polish judge – came into four assessors, terrestrial writer and terrestrial servant called in text twice prawidlnikiem. Of the judicial acts in the most costly for the parties was prepared inventory of estate and initiation of proceedings. All off icers of the court participated in provided court fees but absolutely the largest share in they had courtly judge and terrestrial writer. <!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>